The Role of Guidance and Counseling Teachers in Addressing Verbal Aggression Among Students at SMA Negeri 1 Sindue - Mutia Azzahra; Ridwan Syahran; Ikhlas Rasido; Nur Eka Wahyuningsih Riyadi (FKIP - Universitas Riau, 2026)
This study aims to describe trends in students’ verbal aggressive behavior, the role of Guidance and Counseling (BK) teachers in addressing it, and factors hindering the implementation of BK services at SMA Negeri 1 Sindue. The study employed a descriptive qualitative approach, with the research subjects consisting of three Guidance and Counseling (GC) teachers, one school principal, and five students from SMA Negeri 1 Sindue, selected purposively based on their involvement in GC services and their experiences related to verbal aggressive behavior. The research was conducted from April 7–21, 2026, through observation and in-depth interviews using an interview guide aligned with the study’s focus. The results indicate that students’ verbal aggressive behavior manifests as teasing, coarse language, sarcasm, the use of inappropriate nicknames, and the use of a raised tone of voice, both in person and via social media. Guidance counselors play a role through individual counseling, group guidance, communication ethics training, and collaboration with homeroom teachers and students’ parents. Factors hindering the implementation of guidance and counseling services include low student awareness, limited service time, a large number of students, lack of family support, and the influence of an unfavorable social environment. This study indicates that addressing verbal aggressive behavior requires collaboration between schools, families, and the social environment to ensure that guidance and counseling services can operate more effectively.